Herminium humidicola (Orchidaceae: Orchidoideae), an addition to the Orchid Flora of India - Tsering, J.; Kushwaha, P.S.; Bhattacharjee, A. (Rheedea, 2024)
Herminium humidicola (K.Y. Lang & D.S. Deng) X.H. Jin, Schuit., Raskoti & L.Q. Huan, a rare alpine orchid, is reported here as an addition to the flora of India from Tawang District in Arunachal Pradesh. The miniature sized orchid was found growing at 4530 m elevation. Morphological description of H. humidicola along with photographs of habit and dissected floral parts are provided.